The regulatory complexity of the European Green Deal: Too much too fast? - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2025)
The European Green Deal (EGD) has the intention to transform the EU into a sustainable, resource efficient and competitive economy, ensuring zero net emissions of greenhouse gases (GHG) by 2050. This article illustrates the complex regulatory architecture of the EGD, which is often overlooked. While each of the initiatives is reasonable, their combined impact - often reinforcing each other - could impede Europe's global competitiveness, especially in a fragile economic environment. There are some fields where a thoughtful discussion about implementation deadlines and reporting requirements could help to resolve trade-offs between environmental objectives and competitiveness.
Keywords: A10; K20; L50; 330